Penyelesaian masalah trigonometri dalam kalangan pelajar matrikulasi: Satu kajian kes - Sharimah, Ibrahim (2014)
Competency in the subject of Trigonometry is crucial for the learning of Mathematics at higher levels. Trigonometric Functions are related to algebra, graph reasoning and calculus. Unfortunately, for some students, the initial stages of learning about Basic Trigonometric Functions are fraught with difficulties. As a concequence, students often made errors when solving questions in Trigonometry. Students who have a weak understanding of basic concepts in Trigonometry may faced difficulty in understanding Sine and Cosine functions. The purpose of this study was to explore the understanding of Basic Trigonometry and Trigonometric Functions of Sine and Cosine among students in a Matriculation College. The study also explored the process and common errors students made when solving Trigonometric questions. This qualitative multi-case study was carried out on 60 One-Year Program (PST) students enrolled in three Modules. The data for the study was obtained via a written test, the Trigonometry Understanding Test (UPT), which consisted of six items. The identification of types of understanding was based on Skemp‟s (1982) notion of relational and instrumental understanding, Hiebert and Lefevre‟s (1986) view of conceptual and procedural understanding, and also Gray and Tall‟s (1995) ideas of proceptual knowledge. Four subjects were selected for the clinical interviews and were selected based on their achievement in the UPT. The results of the study showed that the research subjects‟ understanding of Basic Trigonometry was limited to instrumental and procedural understandings. The subjects did not indicate understanding of Basic Trigonometric Functions as procept. Their solutions for the Basic Trigonometry questions were mainly establishing procedures for getting the right answers. The common errors made included carelessness and calculation errors, failure to perform basic multiplication of fractions, and the inability to understand symbolism in Basic Trigonometry, which explained their inability to use the formulas correctly when solving trigonometric questions. Integration of conceptual, procedural and proceptual understanding could contribute to the construction of meaningful understanding of the Trigonometric Functions. This study contributes to the research findings in mathematics education and the formation of policy related to the development of mathematics education curriculum for matriculation students.